INFLUENCE OF EDUCATION AND TRAINING, COMPETENCE ON WORK MOTIVATION AND EMPLOYEE PERFORMANCE AT PT. INSURANCE ASTRA BUANA BANJARMASIN BRANCH - Iskandar, Dahliana (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This article was written with the intention of improving literacy and competence as a result of the motivation for the PT's employees. Astra Buana Cabang Banjarmasin Asuransi The majority of this study's findings can be found in the fact that PT's motivation for literacy and competence is a major factor. Assuransi Astra Buana Cabang Banjarmasin, in which the population runs the risk of acquiring a more powerful variety of mana. In this case, the variable is "Independent" (Pendidikan, Education, and Competence), while the variable is "Dependent" (Kinerja Pegawai), and the variable is "Mediating" (Kerja Motivasi). The analysis was performed using Smart PLS 3.2.9. A number of hypotheses can be found in this study, including the following: positive and significant motivation for the study's completion; positive and significant motivation for the study's completion; positive and significant motivation for the study's completion; positive and significant motivation for the study's completion; positive and significant motivation for the study's completion; positive and significant motivation for the study's completion; positive and significant motivation for the study's completion; positive and significant motivation for the study's completion; positive and significant motivation for the study' Education, Competence, Motivation, and Employee Performance.